Exosome loaded alginate hydrogel promotes tissue regeneration in full‐thickness skin wounds: An in vivo study. Issue 3 (20th November 2019) - Shafei, Shilan; Khanmohammadi, Mehdi; Heidari, Reza; Ghanbari, Hossein; Taghdiri Nooshabadi, Vajihe; Farzamfar, Saeed; Akbariqomi, Mostafa; Sanikhani, Nafiseh S.; Absalan, Moloud; Tavoosidana, Gholamreza
Abstract: Wound healing is known as one of the most complicated biological processes for injured skin caused by surgical, trauma, burns, or diabetic diseases, which causes a nonfunctioning mass of fibrotic tissue. Recent reports have suggested that exosomes (EXOs) secreted by this type of stem cells may contribute to their paracrine effect. In this study, the EXOs were isolated from the supernatant of cultured adipose‐derived stem cells (ADSCs) via ultracentrifugation and filtration. The EXO loaded in the alginate‐based hydrogel was used as a bioactive scaffold to preserve the EXO in the wound site in the animal model. The physical and biochemical properties of EXO loaded Alg hydrogel were characterized and results proved that fabricated structure was biodegradable and biocompatible. This bioactive wound dressing technique has significantly improved wound closure, collagen synthesis, and vessel formation in the wound area. Results offer a new viewpoint and a cell‐free therapeutic strategy, for wound healing through the application of the composite structure of EXO encapsulated in alginate hydrogel. Abstract :